2006
DOI: 10.1016/s1472-6483(10)60631-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum oestradiol and β-HCG measurements after day 3 or 5 embryo transfers in interpreting pregnancy outcome

Abstract: The aim of this study was to assess the clinical value of serum oestradiol concentration 8 days after embryo transfer (D8E2) and beta-human chorionic gonadotrophin (HCG-beta) concentration 12 days after embryo transfer (D12HCG-beta) in the prediction of pregnancy and the outcome of pregnancy following assisted reproduction, taking into account the day of transfer, which was either day 3 (D3) or day 5 (D5). The objective was to improve patient counselling by giving quantitative and reliable predictive informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…As expected, regardless of cryopreservation method, the approximately doubled hCG level in twin pregnancies is consistent with the results of previous studies [29,30]. Low hCG concentration is always associated with non-viable pregnancy in the first trimester [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…As expected, regardless of cryopreservation method, the approximately doubled hCG level in twin pregnancies is consistent with the results of previous studies [29,30]. Low hCG concentration is always associated with non-viable pregnancy in the first trimester [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…Different conditions and duration of embryo cultivation may explain the observations that values of early β-hCG measurements are different following cleavage or blastocyst stage ET. However, the results are conflicting; Zhang et al [12] and Papageorgiou et al [8] have demonstrated lower values after blastocyst cultivation of embryos compared to cleavage stage ET. But subsequently published data on β-hCG levels after cleavage and blastocyst stage ET have shown higher or comparable β-hCG levels after blastocyst transfer compared to cleavage stage ET [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are conflicting; Zhang et al [12] and Papageorgiou et al [8] have demonstrated lower values after blastocyst cultivation of embryos compared to cleavage stage ET. But subsequently published data on β-hCG levels after cleavage and blastocyst stage ET have shown higher or comparable β-hCG levels after blastocyst transfer compared to cleavage stage ET [7,8]. One of the explanations could be that significant development of embryo culture media in the last decade and improved embryo development environment exerted less negative influence on trophoblast production in cultivated embryos in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations